SOSIALISASI MITIGASI DAN SIMULASI GEMPA UNTUK MENINGKATKAN KESIAPSIAGAAN ANAK DI DESA PONDOK MAKMUR KABUPATEN MUKOMUKO, BENGKULU - Fadhia Hayatu Ainni; Ferry Lismanto Syaiful (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
An earthquake is a sudden vibration or movement from within the earth, spreading over the earth's surface. This disaster caused some damage to buildings from light to heavy damage and people who were injured, starved, or left homeless. To avoid and minimize the risk of earthquake disasters, it is necessary to carry out mitigation and simulations to deal with disasters. Earthquake mitigation is everything done to minimize the impact or disaster that an upcoming earthquake will cause. This activity aims to improve and provide essential knowledge and understanding of earthquakes and the steps that must be taken before, during, and after an earthquake. This activity was carried out in Pondok Makmur Village, Air Manjunto District, Mukomuko Regency, Bengkulu Province. The target of this activity is children and youth. The method used in this activity is counseling and simulation of earthquake disaster mitigation to children/teenagers. The counseling method was carried out by providing material about earthquakes, the causes of earthquakes, the consequences of earthquakes, and steps to deal with before, during, and after an earthquake disaster. Meanwhile, the training/simulation is carried out according to the instructions and the steps for dealing with an earthquake. The results obtained from this activity, activity participants gain improvement and knowledge in dealing with disasters, understand the importance of earthquake disaster preparedness, and become better able to deal with earthquake disasters that can occur at any time, and understand instructions and symbols in dealing with disasters. Furthermore, it can be concluded that earthquake mitigation and simulation are very useful for increasing knowledge and preparedness in dealing with disasters and reducing the risk of many victims and damage.